Are the Motivated Learners the Autonomous Ones? - Monica R. Cabanding (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
While theoretical frameworks connect language learner autonomy with identity-oriented motivation, empirical literature often overlooks how pre-service teachers’ long-term professional identities interact with autonomous learning. This study addressed this gap by examining the relationship between pre-service teachers' English learning motivation and their self-assessment as autonomous ESL learners. Utilizing a correlational design, survey data from 243 respondents were analyzed using simple regression analysis. Results indicated high overall motivation (M = 4.19), primarily driven by international orientation (M = 4.45) and professional instrumentality (M = 4.22). Concurrently, respondents demonstrated a high level of learner autonomy (M = 3.92), characterized by strong learning accountability (M = 4.35). However, critical academic vulnerabilities emerged, specifically a dip in oral communication self-efficacy (M = 3.90) and weaknesses in time-related self-management (M = 3.53). Regression analysis confirmed that motivation significantly and positively predicts learner autonomy (β = 0.32, p < .001), accounting for 11% of its variance (R2 = 0.11). This study underscores the critical role of identity-driven motivation in fostering learner independence. Pedagogically, it implies that teacher education programs must pivot from achievement-oriented targets to design holistic curricula that intentionally cultivate global motivations while integrating structured interventions to reinforce behavioral time discipline and oral communication confidence among future language teachers.